Perioperative anxiety in pediatric surgery: Induction room vs. operating room. Issue 4 (28th February 2021) - Wingler, Deborah; Liston, David; Joseph, Anjali; Wang, Yifan; Feng, Haotian; Martin, Lynn
Abstract: Background: Perioperative anxiety can have a profound and lasting effect on children and their parents, with up to 70 percent of children undergoing outpatient surgery experiencing significant physiologic and/or psychological manifestations of anxiety throughout the ambulatory surgical process. The physical healthcare environment itself can contribute to these feelings, substantially impacting the level of anxiety experienced by both the child and their parent. Objective: This study sought to examine whether a difference exists between utilization of an induction room vs. the operating room on child and parent perioperative anxiety for parent present induction. Methods: A single institution multi‐site prospective observational study was conducted with a cohort of 51 healthy children aged 6‐12 years, receiving an outpatient tonsillectomy and/or adenoidectomy and their parent. The methodological approach utilized for this study was Ecological Momentary Assessment. Two psychological measures of anxiety, (i) momentary and (ii) environmental, and one physiologic measure of anxiety (i) electrodermal activity were used. Data were captured separately for child and parent. Results: For children who underwent anesthetic induction in the induction room, all three anxiety responses were significantly lower and exhibited a large positive effect [momentary ( P  = .0002, d  = 1.984, induction room = 3.76, operating room = 7.07), environmental ( P  = .018, d  = 1.160, induction room = 1.72, operating room = 0.85), and electrodermal activity ( P  = .039, d  = 1.007, induction room = 0.76, operating room = 1.51)], as compared to children who were induced in the operating room. Electrodermal activity was also statistically significantly lower, with a large positive effect, in the postoperative environment ( P  = .004, d  = 1.454, induction room = 0.21, operating room = 0.60) for Children who were induced in the induction room, as compared to the operating room cohort. No significant differences were found between parents for momentary and environmental anxiety, and electrodermal anxiety. Conclusions: The nonpharmacological strategy of using an induction room for anesthetic induction of children may be clinically effective in reducing anxiety as compared to an operating room.